Nutritional contents and the utilization of Indonesian native starfruits: Averrhoa dolicocarpa and A. leucopetala (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Damayanti F, Astuti IP, Zulkarnaen RN, Sunarti S. 2020. Nutritional contents and the utilization of Indonesian native starfruit: Averrhoa dolicocarpa and A. leucopetala. Biodiversitas 21: 1303-1309. Averrhoa dolicocarpa Rugayah & Sunarti and Averrhoa leucopetala Rugayah & Sunarti (wild starfruits) are new species of starfruit native to Indonesia. Both species have become plants collection in the Bogor Botanical Gardens (BBG). However, the nutritional content and the utilization of these two species have not been revealed in detail. The species of starfruit that are often widely used by the community are Averrhoa bilimbi and Averrhoa carambola. Therefore, the study aimed to reveal the nutritional content and excavate the potential use of A.dolicocarpa and A.leucopetala. The study was conducted by testing the proximate test, vitamin C content, total phenol, and experiment of starfruit as processed food ingredients. The result showed that the moisture, ash, fat, protein, and total dietary fiber content of A.dolicocarpa and A.leucopetala were comparable to A.bilimbi and A.carambola, while Vitamin C content and total phenol of A.bilimbi were significantly higher than A.dolicocarpa and A.leucopetala. Furthermore, A.dolicocarpa and A.leucopetala can be used as processed food ingredients, such as starfruit fish soup, healthy drinks, pudding, candy, and syrup. But, more comprehensive study on potential uses of A.dolicocarpa and A.leucopetala were still needed to explore information from both species.
Keywords: Processed food ingredients, proximate test, vitamin C, wild starfruit